Can a paleodrought record be used to reconstruct streamflow?: A case study for the Missouri River Basin. Issue 7 (2nd July 2016) - Ho, Michelle; Lall, Upmanu; Cook, Edward R.
Abstract: Recent advances in paleoclimatology have revealed dramatic long‐term hydroclimatic variations that provide a context for limited historical records. A notable data set derived from a relatively dense network of paleoclimate proxy records in North America is the Living Blended Drought Atlas (LBDA): a gridded tree‐ring‐based reconstruction of summer Palmer Drought Severity Index. This index has been used to assess North American drought frequency, persistence, and spatial extent over the past two millennia. Here, we explore whether the LBDA can be used to reconstruct annual streamflow. Relative to streamflow reconstructions that use tree rings within the river basin of interest, the use of a gridded proxy poses a novel challenge. The gridded series have high spatial correlation, since they rely on tree rings over a common radius of influence. A novel algorithm for reconstructing streamflow using regularized canonical regression and inputs of local and global covariates is developed and applied over the Missouri River Basin, as a test case. Effectiveness in reconstruction is demonstrated with reconstructions showing periods where streamflow deficits may have been more severe than during recent droughts (e.g., the Civil War, Dust Bowl, and 1950s droughts). The maximum persistence of droughts and floods over the past 500 years far exceeds those observed in the instrumental record and periods of multidecadal variability in the 1500s and 1600s are detected. Challenges for an extension to a national streamflow reconstruction or applications using other gridded paleoclimate data sets such as adequate spatial coverage of streamflow and applicability of annual reconstructions are discussed. Key Points: Streamflow is reconstructed from an existing paleoclimate drought index Methodological innovation using rCCA addresses very high‐dimensional data set Reconstructed streamflow provides insights into extreme, persistent high, and low flow